Semantic Analysis of Idiomatic Expression Found in Adele's 30 Album - Maysaroh, Siti Maysaroh (JELLE, 2023)
This research aimed the idiomatic expressions contained in Adele’s 30 album. This research analyzes the types of idiomatic expressions found in Adele’s 30 album and explains the semantic analysis. The purpose of this research is to find out the types of idiomatic expressions and semantic analysis of idiomatic expressions found in Adele 30. This study uses the Makkai theory whose object of research is the English idiom in Adele's 30th album. The data were the phrases or words or collocations found in the songs. The data were taken by reading, identifying, analyzing, and interpreting. Then, the data were analyzed by using the theories offered by Makkai related to the topic and finding out the problems in that analysis. A result of this study there were 21 idioms found in the songs and classified into 4 types of idioms offered by Makkai used which are: 16 phrasal verb idioms, 2 tournure idiom, 1 phrasal compound idiom and 2 incorporating idiom. The results of the semantic analysis there are 21 idioms found in the album 30 Adele. Based on Leech's theory, the 21 idioms correspond to 5 types of meaning found in Adele's 30 album.